Child Protection in the Digital Age: A Review of the Preventive Law Child Pornography - Mardika, Nando Yussele; Prabaningrum, Dyah Retna (Magister Hukum Universitas Semarang, 2025)
This research aims to analyse the preventive legal role of the Ministry of Communication and Digital (Komdigi) in combating child pornography content on social media through a normative legal framework. The rise of content containing pornographic elements is increasing in this era of development. Therefore, Komdigi as a government institution has an essential role in handling and preventing pornographic content on social media accounts. This research approach uses the normative method by using written laws and regulations and other legal materials as references. This study concludes that there is a legal basis that regulates child pornography, but there are still shortcomings in the existing legal instruments. Furthermore, in making preventive legal efforts, Komdigi blocks pornographic content through the crawling method and collaborates with other agencies to present child-friendly content. However, in the process, there are still some obstacles. Komdigi carries out a strategic role through the crawling method to block harmful content and cooperates with other agencies to present child-friendly content. The novelty of this study lies in emphasising the institutional-based prevention dimension that supports the implementation of Pancasila values in digital space governance. This study contributes by highlighting Komdigi's strategic prevention function in grounding Pancasila values through digital content governance, an aspect that is not widely discussed in previous legal studies